Strategi Media Sosial Untuk UMKM : Promosi Mudah Dan Kreatif - Lukman, Rica; Lukman, Rica Yulianti; Camelia, Laila Anggun (STIE Amkop Makassar, Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Batuah Village face challenges in increasing their competitiveness and sustainability in the digital era. These challenges include limited understanding and ability to utilize digital platforms to market their products effectively. Batuah MSMEs can utilize social media as an online marketing tool to gain a satisfactory market share. Social media can be used as a means for online sales and promotions. The objective of this activity is to help MSMEs utilize social media as a promotional tool. This activity aims to provide an understanding of the importance of digital marketing in broadening their product awareness. The implementation method includes a social media marketing outreach program, social media account creation, and training.